Repeatibility of agroindustrial characters in sugarcane in different harvest cycles - Silva, Hudsonkléio; Anunciação Filho, Clodoaldo; Bastos, Gerson; Dutra Filho, João; Simões Neto, Djalma (Revista Ciência Agronômica, 2018)
n commercial cultivation of sugarcane, knowledge about the repetition of agroindustrial characters is essential to identify long-lived genotypes in production cycles, which when selected, will contribute to the significant increase in productivity. This work evaluated the agroindustrial performance of 16 sugarcane genotypes in the sugarcane microregion Litoral Norte of Pernambuco in four harvest cycles and the regularity in the repetition of characters. The experiment was conducted in the agricultural area of São José sugar mill, Igarassu, state of Pernambuco, Brazil. The experiment was carried out following a randomized block design with four replications. The variables evaluated were: tons of POL per hectare (TPH), tons of cane per hectare (TCH), fiber (FIB), adjusted POL% (PCC), soluble solids content (BRIX), and total recoverable sugar (TRS). The variance analysis detected significant differences among the genotypes along the four harvest seasons, indicating genetic variability and possibility of success in the selection of superior genotypes. Estimates of repeatability coefficient point to regularity in the repetition of agro-industrial characteristics allowing to identify genotypes with the highest longevity. The genotypes SP79-1011, RB863129, RB92579, RB813804, RB982559 e RB982613 presented best agroindustrial performance, and two evaluations based on TPH and TCH characters are enough to select superior genotypes with 90% predictability of their actual values.